Learning tasks as an assessment tool of competencies in organization of pedagogical practice - O. P. Kazakova (Омский научный вестник: Серия "Общество. История. Современность")
Implementation of the competence approach in education requires the development of a new learning system focused on the formation of competencies by means of each course. The study object is the organization of the pedagogical practice for bachelors, the study subject — learning tasks that allow building the content of the practice according to the target competencies. The article relevance is to develop the evaluation mechanism for assessment of competencies, to include the personal aspect in the evaluation procedure. Scientific novelty of the article is in the development of algorithm of learning tasks design in the organization of the pedagogical practice in correlation with the aimed competences. The purpose of the article is to describe the proposed algorithm on the example of specific competencies, demonstrating the potential of the task approach in assessing the level of competencies with the inclusion of self-reflection. The obtained results can be used both in the process of preparing students of pedagogical universities for pedagogical practice, and in the development of mechanisms for assessing the formation of competencies in any educational institutions